The Siege of Rhodes of 1480: Textual and Iconographic Sources for an Underwater Archaeological Search - Dulska, Anna Katarzyna (The international journal of nautical archaeology, 2025)
The siege of Rhodes by the Ottoman Turks in 1480 was one of the most important military events of the 15th century. Commanded by the Hospitaller Grand Master Pierre d'Aubusson, and played out largely on the surrounding waters, the successful defence has been immortalised in several written sources and art works, yet the small number of underwater archaeological findings attributed thereto is intriguing. To date four wrecks have been indirectly related to one of the three consecutive sieges of 1440, 1480 or 1522. The purpose of this article is to analyse the textual and iconographic sources on the event, the key one being the Descriptio obsidionis Rhodiæ by Guillaume Caoursin (1480), with a view to identifying those elements that are of value in the search for underwater archaeological traces thereof. These sources provide rich information on late medieval maritime warfare and watercraft in the Eastern Mediterranean and suggest that the archaeological potential with regard to the last decades of the Hospitaller presence on the island can be explored further.